Identification and Analysis of Two Genes Differentially Expressed in Spear Leaves of High and Low Yielding Oil Palm - Abu Sapian, Roslinda (2007)
Malaysia is the largest producer and exporter of palm oil with a 50% share of the global oil and fat production. Oil palm is the most productive oil crop with an average yield of about 3 to 4 t/ha/year. The productivity of oil palm is at least 3 to 8 times more compared to other oil-producing crops. Over the past few years, it has become clear that the possibilities for further expansion are now greatly reduced due to the low availability of suitable land. In addition, the increasing competitiveness of other vegetable oil crops, scarcity and cost of labour are some of the reasons driving the requirement to increase the productivity of existing planted land. This study was carried out with the objectives to isolate and analyse the differentially expressed genes in high yielding palms by using suppression subtraction hybridization (SSH) and annealing control primer (ACP) and confirming the differentially expressed gene candidates in high and low yielding palms using reverse northern and northern analysis. The SSH was performed using total RNAs were isolated from spear leaves of high and low yielding oil palm of population OxG and P312. In total, 250 subtracted clones were sequenced and 74.4% of them have significant matches with scores higher than 100 while 21.6% sequences have nonsignificant matches with sequences in the GenBank database. The remaining 4% sequences have no matches to the database. Majority of the genes that were differentially expressed in high yielding palm were associated with primary metabolism (48 sequences) such as glycolysis, oxidative pentose phosphate pathway, amino acid metabolism and acyl lipid metabolism including glucose-6-phosphate dehydrogenase and sucrose synthase. Besides, there were sequences encoding for enzymes in protein synthesis and processing (27 sequences), cell wall (8 sequences), gene expression and RNA metabolism (4 sequences), signal transduction and post-translational regulation (2 sequences), miscellaneous (2 sequences), secondary metabolism and hormone metabolism (2 sequences) and finally, defense and cell rescue (1 sequence). Fifteen clones, eight and seven from population OxG and P312, respectively; were selected for reverse northern analysis. Among these clones, five from population OxG (MAY39, MAY65, MAY79, MAY237 and MAY238) and six from population P312 (MAY133, MAY134, MAY144, MAY148, MAY154 and MAY240) were expressed only in high yielding palms and used as homologous probes in northern blot analysis. Northern analysis, demonstrated equal expression in high and low yielding palm of cytosolic aldolase from population OxG, beta galactosidase and pyruvate dehydrogenase from population P312. Clones encoding glucose-6-phosphate dehydrogenase and sucrose synthase were shown to have higher expression in high yielding palm of both populations, OxG and P312. These genes are closely related to photosynthesis and can be found almost in all plant tissues. They may be potentially useful as molecular markers for the screening of high yielding planting materials.